2006
DOI: 10.2174/156652406779010803
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Roles of Osteopontin in Cell Signaling, Tumor Progression and Angiogenesis

Abstract: Osteopontin (OPN) is a chemokine like phosphorylated glycoprotein that plays important role in cancer progression. Extensive research from various laboratories has demonstrated the likely role of OPN in regulating the cell signaling that ultimately controls tumor growth and metastasis. Several earlier reports indicated that OPN is associated with various cancers; but its functional role in carcinogenesis is still not well defined. Besides the role of OPN in tumor biology, several studies have demonstrated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 109 publications
(153 reference statements)
5
100
0
2
Order By: Relevance
“…Clearly, molecular binding to the cell adhesion molecules integrin and CD44 (4,22) and depletion of growth factors and cytokines (23) could be involved. Of prime importance, however, is the link with prognosis revealed by the present study, in line with the association with malignancy reported earlier (5,24,25).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Clearly, molecular binding to the cell adhesion molecules integrin and CD44 (4,22) and depletion of growth factors and cytokines (23) could be involved. Of prime importance, however, is the link with prognosis revealed by the present study, in line with the association with malignancy reported earlier (5,24,25).…”
Section: Discussionsupporting
confidence: 91%
“…Osteopontin (OPN), a 34 kDa extracellular matrix glycophosphoprotein with a cellbinding domain, plays multifunctional roles in cell adhesion, chemotaxis, macrophage-dependent angiogenesis, prevention of apoptosis, and anchorage-independent growth of tumor cells. Its activity regulates cell-matrix interactions and cellular signaling through binding to integrin and CD44 receptors (4)(5)(6). It has been widely reported to demonstrate altered expression in relation to tumorigenesis, invasion, metastasis and its expression may have prognostic potential in colon (7), lung (8), prostate (9), and breast cancers (10).…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact (if any) of OPN on the CNS and PNS to affect balance and coordination likely involve both positive and negative effects. At the cellular level, the protein has proadhesive, chemotactic and cytokine-like properties, and is involved in a number of physiologic and pathologic events including angiogenesis, apoptosis, inflammation, oxidative stress, remyelination, wound healing, bone remodeling, cell migration and tumorigenesis (Chakraborty et al 2006;El-Tanani et al 2006;Pagano and Haurani 2006). As some of these events lead to neurodegeneration (Maetzler et al 2007;Wung et al 2007) whereas others to neuroprotection (Meller et al 2005;Schroeter et al 2006), the overall outcome in sensorimotor neurons may have been neutralized in the null deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Significance **Po0.01. Control: control IgG; aCD44v7 : anti-CD44v7 antibody 25 What is the evidence for a specific CD44v7 involvement in the inflamed mucosa in CD patients? Apoptotic signaling generally proceeds through the extrinsic and intrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%